(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
The trajectory of the Michoacan priest Francisco Esquivel is reviewed: from seminarian to Cristero captain, and then to priest, based on two unpublished autobiographical writings that increase the heritage of literature on the Cristero War. We analyze the reasons that decided the seminarian to take up arms, as part of the centuries-long controversy in Christian thought about the legitimacy of violence.